2011
DOI: 10.2176/nmc.51.579
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Origin of the Ophthalmic Artery From the Anterior Cerebral Artery -Case Report-

Abstract: Fig. 1 T 1 -weighted magnetic resonance images with contrast medium revealing a well-enhanced mass in the left tentorium, cavernous sinus, and suprasellar region. AbstractA 39-year-old woman presented with left visual disturbance and diplopia. Magnetic resonance imaging revealed a well-enhanced tumor in the left tentorium, cavernous sinus, and suprasellar region. Angiography demonstrated an abnormal origin of the ophthalmic artery from the anterior cerebral artery. The tumor was partially removed by left fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…Excellent embryological explanations for variants exist, but discrepancies are encountered and some explanations remain speculative at best. Li et al (2011) found in their study a female predominance of 77.78% (14 cases) and a unilateral appearance of 88.89% (16 cases), but no right-side or left-side prevalence (ratio 9:8). Eighteen cases of OA variations were reported between 1969 and 2010 (Li et al, 2011), namely with origins from middle meningeal artery (MMA) (10 cases); basilar artery (BA) (2 cases); anterior cerebral artery (ACA) (3 cases); posterior communicating artery (PcomA) (2 cases); and ICA bifurcation (1 case).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Excellent embryological explanations for variants exist, but discrepancies are encountered and some explanations remain speculative at best. Li et al (2011) found in their study a female predominance of 77.78% (14 cases) and a unilateral appearance of 88.89% (16 cases), but no right-side or left-side prevalence (ratio 9:8). Eighteen cases of OA variations were reported between 1969 and 2010 (Li et al, 2011), namely with origins from middle meningeal artery (MMA) (10 cases); basilar artery (BA) (2 cases); anterior cerebral artery (ACA) (3 cases); posterior communicating artery (PcomA) (2 cases); and ICA bifurcation (1 case).…”
Section: Introductionmentioning
confidence: 76%
“…Double OA origin. OA origins at the bifurcation of the ICA (Hamada et al, 1991) or from the terminal branches of the ICA, namely the A1 segment of the ACA (Hassler et al, 1989;Islak et al, 1994;Li et al, 2011;Hannequin et al, 2013), and the M1 segment of the MCA (Weinberg et al, 1981) are reported. Double origins from the ICA may be from the C3 (lacerum) segment and C4 (carotid siphon) segment that correspond to nonmigration of the PVOA and migration of the PDOA (Lasjaunas, 1981;Ogawa, 1990), respectively, or from the carotid siphon corresponding to normal migration of the PVOA (supracavernous ICA siphon) and the presence of an ILT (proximal remnant of the PDOA from horizontal part of carotid siphon) (Padget, 1948;Kam et al, 2003).…”
Section: Ophthalmic Artery Variantsmentioning
confidence: 99%
See 2 more Smart Citations
“…This variation has been frequently explained with the persistence of the PVOA [3, 4, 26, 28, 37, 63], though it more probably involves a persistent recurrent POlfA (Fig. 3) [18].…”
Section: Variations Of the Oa Originmentioning
confidence: 99%